2103 Molecular characterization of lupus nephritis kidneys and blood. (14th December 2022) - Kingsmore, Kathryn M; Shrotri, Sneha; Bachali, Prathyusha; Shen, Nan; Grammer, Amrie; Lipsky, Peter
Abstract : Background/Purpose: Molecular kidney or blood-based biomarkers of lupus nephritis (LN) would provide an advance over standard renal biopsy analysis. Therefore, we analyzed bulk RNA from renal biopsies and paired blood to determine molecular biomarkers of LN, associated with gene expression-determined lupus nephritis endotypes. Methods: Using Gene Set Variation Analysis (GSVA), we analyzed the enrichment of informative modules of co-expressed genes in the biopsies of 76 kidneys derived from patients with LN and matched blood for 71 patients. Gene modules identifying immune/inflammatory cells, resident kidney cells, and metabolic and inflammatory processes were employed where appropriate. Results: GSVA analysis of LN gene expression elucidated four endotypes of LN (figure 1), which were characterized by minimal disease abnormalities (coral); inflammatory disease with minimal kidney cell damage and minimal metabolic dysfunction (yellow); inflammatory disease with marked kidney cell and marked metabolic dysfunction (purple), and little inflammation with markedly decreased kidney cell and markedly decreased metabolic function (black). GSVA analysis of the same LN-derived clusters in the blood of paired patients revealed the two clusters with marked kidney damage (purple and black) had significant enrichment of the LDG signature (figure 2a). The purple cluster was consistently characterized by decreased blood expression of T cell and T cell receptor chain signatures (figure 2b-f), whereas the black cluster exhibited decreased blood expression of the dendritic cell signature (figure 2g). Although production of erythropoietin is known to decrease with chronic kidney disease, 1 expression of EPO was unchanged in the blood across subsets (figure 2h). Conclusions: Transcriptomic analyses support the existence of LN endotypes that progress from acute inflammatory to chronic kidney disease with little inflammation and marked kidney damage. Analysis of the blood of this small cohort of patients with LN suggest that the two most severe molecular endotypes of LN have different profiles than patients with minimal disease. Although the LDG signature can relate to glucocorticoid treatment 2 and T cell lymphopenia is a marker of severe lupus in general, 3 the combination suggests greater suspicion of progression to LN. References: Portolés J, Martín L, Broseta JJ, Cases A. Anemia in chronic kidney disease: from pathophysiology and current treatments, to future agents. Front Med . 2021;8 :642296. Dale DC, Fauci AS, Guerry D IV, Wolff SM. Comparison of agents producing a neutrophilic leukocytosis in man. Hydrocortisone, prednisone, endotoxin, and etiocholanolone. J Clin Invest . 1975;56 (4):808–813. Martin M, Guffroy A, Argemi X, Martin T. [Systemic lupus erythematosus and lymphopenia: Clinical and pathophysiological features]. Rev Med Interne . 2017;38 (9):603–613.